A simple taxonomy for describing the spatio-temporal structure of environmental modelling data. (November 2020) - Harpham, Q.K.
Abstract: Environmental modelling practitioners are now seeking to move forwards together and build standards and technologies with more universal applicability and integration. With so many overlapping environmental modelling technologies and infrastructures being offered and with so many relevant supporting technologies contributing on the periphery, there is considerable scope to articulate and utilise underlying concepts which draw them together. As such, this paper offers the Spatio-temporal Modelling Taxonomy, a simple taxonomy for describing the spatio-temporal structure of environmental numerical modelling data used as input to, or produced as output from environmental numerical models. The taxonomy is motivated from common spatial structures, a set of feature-types to describe observed environmental data and the implementation of the OpenMI integrated modelling standard. It serves as a natural evolution of terminology that is in common use in environmental numerical modelling and is designed to strike the right balance between complexity and utility. It implements a structured, theoretical framework, whilst being essentially practical in nature to apply to the 'real world' facing numerical modellers and those seeking to integrate environmental numerical models and the data supporting them. Highlights: A simple taxonomy for describing the spatio-temporal structure of environmental numerical modelling data. Motivations for the design of the taxonomy. Structured derivation of the taxonomy. Use case examples of application in a variety of modelling domains.